Collapse Analyses of Pre- and Low-Code Italian RC Building Types - Vincenzo Manfredi (Buildings)
In seismic risk analyses, collapse assessment is of critical importance, as it leads to most injuries and fatalities, as well as significant economic losses. In this paper, the seismic collapse response of some 3D prototypes representative of the 1970s Italian reinforced concrete building stock has been analyzed. The considered prototypes have been selected based on two of the most important typological parameters, namely the number of storeys (three types: 2-, 4-, and 6-storey) and the design level (two types: gravity load design, representative of pre-code types, and earthquake-resistant design with low lateral load intensities without anti-seismic details, representative of low-code types). Incremental non-linear dynamic analyses have been performed along the two in-plane directions using a set of 20 real signals scaled up to collapse. The inter-storey drift ratio values at collapse have been analyzed to estimate the mean and dispersion values of the best-fitting distribution functions. These results can be used as capacity thresholds for assessing seismic performance in numerical analyses. Fragility curves have also been derived using different intensity measures to estimate the exceedance probability of collapse, accounting for their inherent efficiency, to be used in seismic risk analyses. Results have been compared to provide valuable insights into the influence of the considered typological parameters on collapse.